COMPARISON OF HANDGRIP STRENGTH BETWEEN RIGHT-HAND AND LEFT-HAND UNIVERSITY MALE BADMINTON PLAYERS - Ayesha Siddiqa; Sofia Amjad; Yasmeen Tabassum; Muhammad Zafar Iqbal Butt (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
Badminton is a popular sport worldwide that requires fast and powerful shots and agile footwork. Badminton is all about the wrist and the true power of any badminton shot comes from a combination of your wrist action and the racket swing. The present study aimed to compare the handgrip strength between right-handed and left-handed university badminton players. For this purpose, a total no. of 30 (right-handed n=15 and left-handed n=15) male badminton players ages 19-25 years old from the Department of Sport Sciences and Physical Education, University of the Punjab Lahore were selected for this study. All subjects were assessed for their handgrip strength using a hand-held dynamometer. Three trials were given for each of the participants and an average score was recorded. Descriptive statistics of handgrip strength were analyzed in terms of mean and standard deviation. The results concluded that there was a significant difference (p<0.05) between the mean score of hand grip strength of the left hand and right hand of badminton players. Accordingly, to statistical values, Badminton players had more left-hand strength than right-hand at University Level.